2012
DOI: 10.1007/s00122-012-1819-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of adult plant resistance to stripe rust in the wheat cultivar Cappelle-Desprez

Abstract: Following the appearance of stripe rust in South Africa in 1996, efforts have been made to identify new sources of durable resistance. The French cultivar Cappelle-Desprez has long been considered a source of durable, adult plant resistance (APR) to stripe rust. As Cappelle-Desprez contains the seedling resistance genes Yr3a and Yr4a, wheat lines were developed from which Yr3a and Yr4a had been removed, while selecting for Cappelle-Desprez derived APR effective against South African pathotypes of the stripe ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(80 citation statements)
references
References 59 publications
5
75
0
Order By: Relevance
“…QYrEDWL.par-4B.1 , spanning the centromeric region of chromosome 4B, has been mapped in the same region of previously reported QYr-4B in French durum wheat ‘Sachem’ (Singh et al, 2013) and QYr.ufs-4B in South African spring wheat ‘Palmiet’ (Agenbag et al, 2012). QYr-4B , tagged by wPt-0872, was a pleiotropic QTL conferring effective resistance to both stripe rust and stem rust in the field.…”
Section: Discussionsupporting
confidence: 62%
“…QYrEDWL.par-4B.1 , spanning the centromeric region of chromosome 4B, has been mapped in the same region of previously reported QYr-4B in French durum wheat ‘Sachem’ (Singh et al, 2013) and QYr.ufs-4B in South African spring wheat ‘Palmiet’ (Agenbag et al, 2012). QYr-4B , tagged by wPt-0872, was a pleiotropic QTL conferring effective resistance to both stripe rust and stem rust in the field.…”
Section: Discussionsupporting
confidence: 62%
“…In the current study, six potentially novel QTL for resistance to stripe rust were identified in combined and individual environment analyses (Table 2) and one additional candidate novel QTL was detected exclusively in club wheat (Supplementary Table 10). The novel genomic region identified on 2DS at 28.0 cM is approximately 90–100 cM away from previously reported QTL for stripe rust response on 2DS using bi-parental populations (Bariana et al, 2001; Suenaga et al, 2003; Mallard et al, 2005; Melichar et al, 2008; Lu et al, 2009; Agenbag et al, 2012). Naruoka et al (2015) recently reported a stable APR locus on 2DS (stable in nine environments) using GWA in a winter wheat association panel.…”
Section: Discussionmentioning
confidence: 53%
“…These results suggest that they are likely novel Pst resistance loci (Figure 6). IWA167 , one of the most significant QTL detected in this study, was mapped within the flanking markers of a weak QTL from Cappelle Desprez ( QYr.ufs-6D ; Agenbag et al 2012). However, the peak of QYr.ufs-6D was mapped on the long arm of chromosome 6D, whereas IWA167 is in the short arm.…”
Section: Discussionmentioning
confidence: 95%